Marxism As the Philosophy of History: Advanced Arguments of Merleau-Ponty: Revisiting Marxism as the Philosophy of History in the Contemporary Intellectual Climate (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Merleau-Ponty advanced an argument in the earlycold war years that Marxism was the philosophy of history.  This article re-examines this position.  It argues that not only in spite of butbecause of today’s changed situation, the importance and validity of hisargument remains.  He argues that inspite of its many errors and weaknesses Marxism is irrefutable as a critique ofany possible humanism that is not hypocritical. Marxism’s teleology and scientificity are also re- examined.  The article critically (and polemically)considers the context of reception for such discussions and argues thatthere is something terribly wrong in our contemporary intellectual climatewhereby some positions (however well argued) simply can no longer get a hearingonce judged to have gone out of fashion. It is argued that this is particularly dangerous in political philosophicaldiscourse.